Mengenalpasti corak pembelian pelancong antarabangsa terhadap produk cenderamata di Malaysia - Sarman, Zaiton (2007)
The nature of humans is to return from traveling with a souvenirs of the experience. The purchase of souvenirs by a tourist serves as a tangible way of capturing or suspending in time an otherwise intangible experience. The purpose of this study is to identify souvenirs purchase patterns of foreign tourist in Malaysia, focusing on Kuala Lumpur and Melaka City. Souvenirs product, product attributes and store attributes were analyzed for the significant between demographic variable and the factors that influencing in souvenirs purchasing . Means score and cross tab were administered. The survey finding, revealing souvenirs shopping patterns of tourists visiting Kuala Lumpur City and Melaka City, suggest the their influenced by many factors, including length of shopping time, purpose of traveling, forms of travel, annual income level, product attributes, store attributes, and reason for purchasing. Further analysis suggest what types of souvenirs are favored by foreign tourists and why. These findings potentially assist in improving souvenir production, methods of display at stores, tourist satisfaction, and income earnings of producers and store operators, a process which would contribute to the socioeconomic well-being and prosperity of the host community. Since purchasing souvenirs is also a indispensable tourism experience for foreign tourists, the contributes to this research theme, with applications for destinations in Malaysia and elsewhere.